Performance, membrane fouling control and cost analysis of an integrated anaerobic fixed-film MBR and reverse osmosis process for municipal wastewater reclamation to NEWater-like product water - Liu, Hang (2022)
To relieve the increasing pressure on water scarcity, reclamation and reuse of municipal wastewater represent a global trend. However, the current process for high-grade reclaimed water production faces increasing pressure because of the intensive energy consumption, excessive sludge generation, highly complicated process configuration and large footprint. To tackle these challenges, an integrated anaerobic fixed-film membrane bioreactor (AnfMBR) and reverse osmosis (RO) process was proposed in this study for municipal wastewater reclamation to high-grade product water. Results showed that the product water of the proposed process could meet the typical NEWater quality. As fixed anaerobic biofilms were adopted in the reaction chamber of AnfMBR, the intensity of gas sparging for membrane scouring was significantly reduced due to the low suspended solids (SS) in mixed liquor. It was found that the membrane fouling in AnfMBR was dominated by the cake layer, while biofilms and organic substances were the major components in RO foulants. Compared to the current NEWater production process, about 35.7% reduction in total cost could be achieved in the AnfMBR-RO process due to the significantly improved energy efficiency. Consequently, the proposed AnfMBR-RO process appeared to be a promising and feasible alternative to the current municipal wastewater reclamation process.